The Role of Group Supportive Psychotherapy on Quality of Life and Its Relationship to Heart Rate Variability and Serum Serotonin Levels in End-Stage Renal Disease (ESRD) Patients undergoing Chronic Hemodialysis - Jeger, D.P.; Shatri, H.; Lukman, P.R.; Nugroho, P.; Kandarini, Y.; Dwipayanti, N.M.A. (South Eastern European Journal of Public Health, 2024)
Introduction: End-stage renal disease (ESRD) significantly impacts patients’ physical and psychological health, marked by diminished quality of life,decreased heart rate variability (HRV),and reduced serum serotonin levels. ESRD patients undergoing chronic hemodialysis experience heightened autonomic dysfunction, increased sympathetic tone, and multiple systemic complications, leading to profound emotional and social challenges. Objectives: This review explores the role of group supportive psychotherapy in addressing these challenges by assessing its impact on quality of life, HRV, and serotonin levels in ESRD patients. Methods: A comprehensive analysis of existing literature was conducted to evaluate the psychosocial and physiological effects of supportive psychotherapy on ESRD patients undergoing hemodialysis. Factors examined included quality of life metrics, HRV as an indicator of autonomic function, and serotonin regulation. Results: Group supportive psychotherapy has been shown to offer significant benefits for ESRD patients. It fosters emotional resilience, improves coping mechanisms, and provides communal support, leading to better stress management and enhanced quality of life. Psychotherapy interventions positively influence HRV by modulating autonomic balance and reducing sympathetic overactivity. Additionally, addressing psychological well-being can aid in stabilizing serotonin levels, mitigating mood disturbances commonly observed in these patients. Conclusions: Group supportive psychotherapy is a valuable, non-pharmacological intervention that enhances the overall well-being of ESRD patients undergoing hemodialysis. By providing holistic emotional and psychological care, it can improve HRV, elevate quality of life, and contribute to better mood regulation through serotonin balance. Implementing supportive psychotherapy as part of a comprehensive care strategy is recommended to address the multifaceted needs of this patient population.